Giving birth on my own terms: Using systems thinking and user-centered design to empower women and improve childbirth experience (2022)
This thesis aims, to propose a feasible solution to the obstetric violence suffered by women in Colombia. Through design approaches such as User Centered Design and Systems Thinking, it is intended to explore obstetric violence to understand it as a phenomenon, its causes, and a possible solution that improves the childbirth experience of women in Colombia.